2016
DOI: 10.1093/cid/civ1206
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Assessment of Rotavirus Vaccine Effectiveness in Zambia

Abstract: We observed a higher point estimate for VE against increased severity of illness compared with milder disease, but were not powered to detect a low level of VE against milder disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 15 publications
0
41
0
Order By: Relevance
“…The design of the original study was described in detail elsewhere [2]. Briefly, children were eligible if they were aged 0-59 months; admitted to the inpatient department or under care in the outpatient department; and caregiver verbal confirmation of child presenting with diarrhoea (defined as the passing of ≥3 abnormally loose stools in the past 24 hrs).…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The design of the original study was described in detail elsewhere [2]. Briefly, children were eligible if they were aged 0-59 months; admitted to the inpatient department or under care in the outpatient department; and caregiver verbal confirmation of child presenting with diarrhoea (defined as the passing of ≥3 abnormally loose stools in the past 24 hrs).…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Following the World Health Organisation recommendation, several countries have introduced rotavirus vaccines (RVs) into their national immunisation schedules with an observed significant impact on reduction of rotavirus associated morbidity and mortality [1]. Zambia implemented RVs in the national expanded programme on immunisation starting in Lusaka province in 2012 and scaling up to countrywide by end of 2013; becoming the 17 th GAVI eligible country to do so [2]. Over the period, significant reduction in acute gastroenteritis-associated in hospital morbidity and mortality has been recorded with the greatest reduction observed among children aged <1 year [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is consistent evidence from clinical trials that RV have lower efficacies in low-and middle-income countries (LMIC): vaccine efficacies are 80 to 90% in high-income countries (HIC) and 40 to 60% in LMIC (3)(4)(5)(6)(7)(8). Indeed, there is growing evidence from vaccine effectiveness studies emerging from the field that in real-life use, vaccine effectiveness is also consistently lower in LMIC (9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Although subsequent trials from low and middle income countries (LMICs) showed much lower efficacy rates between 40 and 60% [7][8][9][10], the public health impact in these high burden settings was still compelling enough to continue the immunization campaigns. Several other vaccines are in the developmental and licensure phase such as Rotavin ™ and RotaVac ™ which have partial or restricted licensure in China, Vietnam and India [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…LMICs researchers are now also beginning to generate more information on vaccine effectiveness in their respective locations that has shown that vaccine responses have continued to be sub-optimal [7][8][9][10][15][16][17].…”
Section: Introductionmentioning
confidence: 99%